Impact of the Process Genre Approach on the Management Students’ Business Writing Skills - Bonala Kondal (ELS Journal on Interdisciplinary Studies in Humanities, 2020)
In the present corporate world, it is prominent to hone business writing skills among students for becoming good management professionals. Writing is foremost and significant skill in the business world, but most of the students lack proficiency in their writing. The present paper attempts to explore the impact of the process genre approach in teaching business writing skills to the management professionals. The sample of the study consists of 40 management students from a professional college and 32 teachers of English who were working in sixteen different professional colleges. In order to collect the data, the questionnaires were administered to the students as well as to the teachers. Post analysis of the data, it was found that management students’ business writing skills had a positive impact when the process-genre approach incorporated in teaching and learning processes.  Hence, it is concluded that the use of the process genre approach for teaching business writing to the management students during the intervention had become successful in achieving the desired goal.  It also aided the students in developing better writing proficiency and enhancing their business writing skill.